Life of Pi : a novel - Martel, Yann. (New York : Harcourt, 2001)
Possessing encyclopedia-like intelligence, unusual zookeeper's son Pi Patel sets sail for America, but when the ship sinks, he escapes on a life boat and is lost at sea with a dwindling number of animals until only he and a hungry Bengal tiger remain.
Man Booker Prize for Fiction, 2002.
Keywords: Shipwreck survival -- Fiction; Human-animal relationships -- Fiction; Pacific Ocean -- Fiction; Storytelling -- Fiction; Teenage boys -- Fiction; Ocean travel -- Fiction; Zoo animals -- Fiction; Orphans -- Fiction; Tiger -- Fiction; Psychological fiction; Adventure fiction